Vocal sharing and individual acoustic distinctiveness within a group of captive orcas (Orcinus orca) - Kremers, Dorothee; Lemasson, Alban; Almunia, Javier; Wanker, Ralf (Journal of Comparative Psychology, 2012)
International audience Among vocal learners, some animal species are known to develop individually distinctive vocalizations, and others clearly learn to produce group signatures. The optimal vocal sharing hypothesis suggests that vocal divergence and convergence are not compulsorily exclusive and both can be found at different levels in a given species. Being individually recognizable is socially important even in species sharing vocal badges. Acoustic divergence is not systematically controlled as it can simply be due to interindividual morphological differences. We tested that hypothesis in a species known to learn their family vocal dialect socially: the orca (Orcinus orca). We identified 13 different call types, including some shared by all group members, some shared only by 2 or 3 individuals, and others particular to 1 individual. Sharing was higher between males than between females. Three of our 4 orcas each produced a unique call type, which was preferably emitted. The call types shared by all orcas still presented individual acoustic distinctiveness that could, to some degree, be explained by morphological differences. We found evidence for strong similarities between some of the call types of our captive orcas and the call types of their ancestors, which are Canadian and Icelandic free-ranging orcas. Our findings suggest that captive orcas use a complex vocal repertoire enabling each individual to produce sounds that are similar to some of their partners', which might be used as social badges to advertise their preferential bonds, as well as individual-specific calls. Our findings open new lines of research concerning the functional value of a balanced "diverging-converging" vocal system.